Sri Lanka macroeconomic challenges a tale of two Deficits. - Weerakoon, Dushni; Asian Development Bank (Manila,Philippines Asian Development Bank, [2019])
Fiscal dominance has been a persistent feature of Sri Lanka macroeconomic landscape. This has manifested itself in high macroeconomic volatility and the country has seen frequent balance of payments crises. The paper makes policy recommendations to deal with these issues.
Keywords: Public administration -- Sri Lanka; Electronic book